2017
DOI: 10.1155/2017/5191046
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellic Acid Production by Different Fermentation Systems Using Citric Pulp as Substrate/Support

Abstract: Gibberellic acid (GA3) is an important phytohormone, a member of gibberellins family, which acts as a promoter and regulator of plant growth. This study aimed to evaluate GA3 production by Fusarium moniliforme LPB03 and Gibberella fujikuroi LPB06 using different techniques of fermentation, solid state fermentation (SSF), submerged fermentation (SmF), and semisolid state fermentation (SSSF), and different types of bioreactors. In all techniques, citric pulp (CP), a subproduct obtained from the extraction of ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 40 publications
0
19
0
2
Order By: Relevance
“…Different substrates have been used for GA 3 production in SSF, such as citric pulp [130][131][132], pigeon pea pod, pea pod, corn cub, sorghum straw [133], coffee husks [134], wheat bran [135][136][137] and others (Table 6). Media supplementation with carbon sources can be carried out using sucrose and starch.…”
Section: Plant Growth Hormonesmentioning
confidence: 99%
“…Different substrates have been used for GA 3 production in SSF, such as citric pulp [130][131][132], pigeon pea pod, pea pod, corn cub, sorghum straw [133], coffee husks [134], wheat bran [135][136][137] and others (Table 6). Media supplementation with carbon sources can be carried out using sucrose and starch.…”
Section: Plant Growth Hormonesmentioning
confidence: 99%
“…The Taguchi method was successfully used to examine the effects of different medium components such as carbon and nitrogen sources influencing the production of various microbiology metabolites [21][22][23][24]. In this study, the L25 Taguchi design was used to determine the relative effect of the selected factors (sesame bark, wheat straw, date waste, NaNO 3 , urea, and (NH 4 ) 2 SO 4 on GA3 production by B28 strain Fusarium oxysporum and also to choose the most adequate substrate among the studied ones.…”
Section: Optimization Of Ga3 Production By the Taguchi Methodmentioning
confidence: 99%
“…Therefore, GA3 production increased by the use of date waste and wheat straw at its higher levels. Several studies have reported the production of GA3 in SSF using waste and byproducts [9,10,24]. Panchal and Desai [26], who investigated the production of GA3 of Fusarium moniliforme in SSF, used the commercial wheat bran (CWB) mineral salt acid as a solid substrate.…”
Section: Optimization Of Ga3 Production By the Taguchi Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…In an SSF system, the selection of support/substrate materials is crucial, as it may provide nutrients, serve as a support material, and induce product synthesis. Different types of substrate materials have been tested for GAs production, including wheat bran (Agosin et al, 1997;Bandelier et al, 1997), Coffee husk (Machado et al, 2002(Machado et al, , 2004, citric pulp (Rodrigues et al, 2009;de Oliveira et al, 2017), Pigeon pea pods, Corncobs, Sorghum straw (Satpute et al, 2010) etc. The use of these plant derived materials/wastes reduced the production cost whereas all resulted in a high productivity of GAs.…”
Section: Fermentation Typesmentioning
confidence: 99%